1991
DOI: 10.1177/00220345910700070801
|View full text |Cite
|
Sign up to set email alerts
|

Upper Central Incisor and Canine Tooth Crown Size in 47,XXY Males

Abstract: Enamel and dentin thicknesses were measured in permanent tooth crowns of 47,XXY (Klinefelter syndrome) males. In 47,XXY males, enamel thickness in maxillary central incisors was significantly greater than that in control males or females, and dentin thickness in incisors and canines was significantly greater than that in control females, but smaller than that in normal males. These findings confirm the concept that human dental growth is affected by sex chromosomes. Amelogenesis is promoted by both X and Y chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
4

Year Published

1992
1992
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 20 publications
3
41
0
4
Order By: Relevance
“…Results from studies on individuals with chromosomal aneuploides shed some light on the role of sex-linked genes in regulating the overall relative contribution of these two dental hard tissues to overall tooth size (e.g., Alvesalo and Tammisalo, 1981;Alvesalo, 1985;Alvesalo et al, 1985Alvesalo et al, , 1987Alvesalo et al, , 1991. The amelogenin (an enamel protein) gene lies on the X chromosome, and individuals with X chromosome aneuploides (e.g., the sequence 46,XX to 47,XXX) possess proportionately thicker enamel with no changes in the amount of dentine.…”
Section: Discussionmentioning
confidence: 99%
“…Results from studies on individuals with chromosomal aneuploides shed some light on the role of sex-linked genes in regulating the overall relative contribution of these two dental hard tissues to overall tooth size (e.g., Alvesalo and Tammisalo, 1981;Alvesalo, 1985;Alvesalo et al, 1985Alvesalo et al, , 1987Alvesalo et al, , 1991. The amelogenin (an enamel protein) gene lies on the X chromosome, and individuals with X chromosome aneuploides (e.g., the sequence 46,XX to 47,XXX) possess proportionately thicker enamel with no changes in the amount of dentine.…”
Section: Discussionmentioning
confidence: 99%
“…(1976). However, the finding is consistent with studies of individuals with chromosomal abnormalities <e.g., Alvesalo et at., 1991), implying that human sex chromosomes influence the thickness of dental aowns, and also with recent molecular genetic investigations (Lau et at., 1989;Nakahori et at, 1991;Salido et at., 1992) showing that genes on the human sex chromosomes influence enamel formation. It has been hypothesized further that sequence differences between the genes on X and Y chromosomes contnbute to the observed sexual dimorphism in tooth size (Lau et at, 1990;Fmcham et at, 1991).…”
Section: Multivariate Analysesmentioning
confidence: 99%
“…Yet the female mice, like female children with Turner syndrome who lack BGN [Heegard et al, 1997] and may fail to express another factor that controls BGN expression, showed greater differences in tooth volume than male mice. In that respect, it is interesting to note that human males with Klinefelter syndrome (XXY), who may express extra BGN, have larger permanent tooth crowns than normal males and females [Alvesalo et al, 1991]. There are no consistent reports of sexual dimorphism in crown size in humans and primates, although several studies have addressed this question [Dempsey et al, 1999;Koppe and Swindler, 2004;Anderson, 2005;Harris and Lease, 2005].…”
Section: Sex-dependent Differences In Wt and Bgn-defi Cient Teethmentioning
confidence: 99%